Sobre algunas aves de la estancia Guaycolec, provincia de Formosa, Argentina - Ramírez-Llorens, Patricio; White, Emilio E.; Rotundo, Marcelo (Nuestras Aves, 2003)
Este artículo no cuenta con un resumen.